The Position of Deoxyribo Acid Nucleid Results as Digitization Evidence in Realizing Child Rights Reform in Indonesia - Robert Libra; Okfalisa, Okfalisa; Aslati, Aslati (Dinasti Research, 2024)
Technological progress continues along with changing times. The application of technology has penetrated various aspects of daily life, making it more practical. Often, problems arise when the father does not recognize his child, which results in the child losing his rights, including the right to receive love from his own father. To overcome this, MK Decision no. 46/PUU-VIII/2010 concerning Review of Article 43 paragraph (1) of Law no. 1 of 1974 concerning Marriage changed the paradigm of evidence by allowing the use of DNA testing technology to determine the lineage of children outside of marriage. The formulation of the problem raised in this research is 1) how is the role of digitalization in realizing children's rights, studying the decision of the Supreme Court of the Republic of Indonesia; and 2) how to reform children's rights in Indonesia in the era of digitalization 4.0. The research method uses normative juridical with a statutory regulatory approach and conceptual approach. The research results show that several existing decisions often refer to digital evidence in the form of DNA (Deoxyribo Nucleid Acid) and decisions that mostly use this evidence will protect children's rights and end up maximizing the protection of children's rights when the parents deny the status of their child in front of the judge. Then the process of proving children's rights using digitized evidence can be carried out by adopting this evidence in Law no. 7 of 1989 concerning Religious Courts to create legal certainty for families, especially for children themselves.